Does Mental Illness Impact the Incidence of Crime and Victimisation among Young People?. Issue 1 (2nd January 2017) - Cashman, Emma L; Thomas, Stuart DM
Abstract : While the high prevalence of offending and victimisation among young people is well established, no study to date has compared official crime records of young people with mental illness with those without mental illness. This case linkage study sought to determine whether young people with a formal history of mental illness were more likely to have official histories of offending and victimisation than young people who had no recorded histories of mental illness. Results suggested that young people with a history of mental illness are particularly vulnerable to violence. While a weak association was established between violent offending and mental illness, a stronger relationship was found between victimisation and mental illness, especially violent victimisation. Consistent with literature regarding the victim–offender overlap, a history of offending placed young people at a substantially higher risk of victimisation. Implications of these results are discussed in the context of how public mental health services could better protect these vulnerable young people.